Teaching psychiatric nursing with films during the COVID‐19 pandemic: A qualitative study. - Arkan, Burcu; Bostanlı, Aylin (Journal of Psychiatric & Mental Health Nursing (John Wiley & Sons, Inc.), 2024)
Accessible summary: What is known on the subject: Interactive learning environments are known to be among the most effective methods used in education.Some of the interactive methods used in psychiatric nursing education are simulations, group discussions, case studies and video and film presentations. In psychiatric nursing education, cinematic films are among the online methods used.It is known that films used in psychiatric nursing education are useful for understanding mental disorders, the nurse–patient relationship, the roles of the nurse and the therapeutic environment. What the paper adds to existing knowledge: The COVID‐19 pandemic deeply affected nursing education, and the difficulties faced gave rise to many new perspectives. After this period, it is of prime importance to update the nursing curriculum and develop new strategies in clinical practice.Teaching with films can help students to understand people's feelings, make sense of them and empathize. This method can have an emotional impact on student nurses and take learning to a deeper level beyond simple theoretical understanding. What are the implications for practice: The findings of the study suggest that teaching through film is an effective method that can be used practically in psychiatric nursing education.Standardizing these practices may be an effective strategy for developing students' professional identity as nurses.This study is focused on undergraduate students, but has implications for nurses in continuing education and professional development of nurses in developing a positive perspective towards psychiatric patients, increasing self‐awareness and reducing prejudices. Introduction: The COVID‐19 pandemic affected many areas of life and had a negative effect on education. Aim/Question: This study investigated the impacts of using film as a method of education in students who were taking Psychiatric Nursing class during the COVID‐19 pandemic, examining how this method contributed to theoretical and clinical practices of the students, their personal development and their viewpoint on psychiatric patients. Method: This study adopted a qualitative research design. The study data were collected from 15 nursing students in June 2022. Interviews were conducted, audiotaped and transcribed verbatim. Results: The method of education via film made contributions such as better theoretical understanding of the subjects taught, acquisition of analytical thinking skills and greater awareness of professional nursing skills and care practices. The students developed their professional perspectives, and their motivation increased. Discussion: Using film is effective and practical when used in psychiatric nursing education. Standardizing these practices may be an effective strategy for developing students' sense of their identity as professional nurses. Implication for Practice: This study relates directly to undergraduate students and also has implications for nurses undergoing continuing education and professional development.